1990
DOI: 10.1021/es00079a004
|View full text |Cite
|
Sign up to set email alerts
|

Modeling plant uptake of airborne organic chemicals. 1. Plant cuticle/water partitioning and molecular connectivity

Abstract: Molecular connectivity indexes were tested with regard to their ability to describe the cuticle/water partitioning for a variety of organic chemicals. A model is derived that accounts for 99% of the variation in the published cuticle/water partition coefficients (Kcv¡), which cover the range of 8.5 orders of magnitude. It is shown that the molecular size is directly proportional to the cuticle/water partition coefficients. It is also the most important structural feature that accounts for 89% of the variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(34 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…Indeed, in work with modelling plant uptake of xenobiotics the VOC characteristics that are included are often the 1-octanol/water partition coefficient and the Henry's law constant or the air/water partition coefficient (Bacci et al 1990;Riederer 1995;Trapp 2007). The ease of entry through the cuticle has been shown to be directly proportional to the molecular size of the compound (Sabljic et al 1990). These investigations are conducted within an agricultural or outdoor bioremediation context with pollutants such as pesticides or PAHs, and much is based on theoretical calculations.…”
Section: Removal Of Vocs By Aboveground Plant Partsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in work with modelling plant uptake of xenobiotics the VOC characteristics that are included are often the 1-octanol/water partition coefficient and the Henry's law constant or the air/water partition coefficient (Bacci et al 1990;Riederer 1995;Trapp 2007). The ease of entry through the cuticle has been shown to be directly proportional to the molecular size of the compound (Sabljic et al 1990). These investigations are conducted within an agricultural or outdoor bioremediation context with pollutants such as pesticides or PAHs, and much is based on theoretical calculations.…”
Section: Removal Of Vocs By Aboveground Plant Partsmentioning
confidence: 99%
“…The relationship between removal and VOC identity may be further explored by looking at parameters such as molecular size, 1-octanol/water coefficient and Henry's law constant (Bacci et al 1990;Riederer 1990;Sabljic et al 1990;Trapp and Matthies 1995). Uptake of pollutants has earlier been noted to be independent of functional group or molecular weight (Bromilow and Chamberlain 1995), but for degradation studies, functional groups may be a relevant factor (Korte et al 2000).…”
Section: Voc Identitymentioning
confidence: 99%
“…In addition to gas-phase reactions, heterogeneous reactions are known to play a key role in BVOC chemistry (Shen et al, 2013). It has been suggested that some of the BVOCs produced by foliage could be attached to the epicuticular waxes (Sabljic et al, 1990;Welke et al, 1998), providing additional protection against oxidants, but scientific knowledge on this issue is currently very limited. At least in theory BVOCs also affect the formation of water films on leaf surfaces (Rudich et al, 2000;Sumner et al, 2004), thereby enhancing O 3 deposition mediated by surface wetness.…”
Section: Introductionmentioning
confidence: 99%
“…In both approaches it is lipid, wax, or cutin phases that apparently absorb most of the chemical and are thus of primary interest when evaluating and correlating partitioning. The significance of lipids, waxes, and cutin as sites of absorption and accumulation of organic chemicals has been discussed and studied by numerous authors including Kirkwood [8], Sabljic and Güsten [9], Kerler and Schönherr [10], Schö nherr el al. [11], and Reischl et al [12].…”
Section: Introductionmentioning
confidence: 99%